The beginning of life according to Iamblichus. On De anima embryology (Circe de clásicos y modernos, 2021)
Section 32 of Iamblichus’ De anima begins with the analysis of three possible explanations about the way the soul enters the body. The first two are anonymous while the third one is attributed by the philosopher of Chalcis to Plotinus’s followers. The theme is announced in the previous section (31) where from the beginning a reference to “Hippocrates, the Asclepiade” can be read connected to a previous lost sentence which would mark the argument’s outset. As a possible source for Iamblichus, Porphyry is often cited. Porphyry includes views from Hippocrates, from an anonymous philosopher, and from Numenius of Apamea about the moment when life begins and the soul naturally becomes associated with the body. In the development of the aforementioned sections 31 and 32, an implicit knowledge of the embryological hypotheses of the time is appraised.
Keywords: Iamblichus; embryology; Neoplatonism; Stoicism